An exploration of ethnomathematical approaches in the teaching and learning of Grade 6 Geometry - Poo, Freda Mmapula (University of the Free State, 2024)
This study aimed to explore ethnomathematical approaches in the teaching and learning grade 6 geometry. The study was prompted by alarming learner performance trends on national assessments and international evaluations, such as Trends in International Mathematics and Science Study (TIMSS). Results from these assessments, including the national assessment Diagnostic Report (DBE, 2014), revealed a persistent pattern of underachievement in geometry among learners, demonstrating a critical need for targeted support and an innovative approach to enhance teaching and learning in this content area. Scholars such as Abiam, Abonyi, Ugama and Okafor (2016) and Nkopodi and Mosimege (2009) identified that the high failure rate among learners might be due to methods used by teachers, teachers’ inability to connect learners learning to cultural experiences, teachers limited knowledge of ethnomathematical approaches and how to integrate them into the teaching of geometry. In answering the research question: How can ethnomathematical approaches be explored in the teaching and learning Grade 6 geometry? The study explored: (1) Grade 6 teachers' understanding and experience of ethnomathematical approaches, examining their ability to integrate cultural practices into geometry instruction. (2) Grade 6 learners’ familiarity with Ndebele cultural artefacts as teaching and learning resources, assessing their knowledge of the embedded mathematical concepts and their cultural significance (3). Women Knowledge Holders’ expertise as custodians and designers of Ndebele cultural artefacts, uncovering their intuitive mathematical knowledge, its application in crafting the cultural artefacts, and most importantly, their collaboration with teachers in implementing ethnomathematical approaches. Vygotsky’s theory of socio-cultural learning guided the study. A qualitative ethnographic design was employed. Two sampling procedures were used to select participants. Purposive sampling was used to intentionally choose teachers and learners with expertise and experience to answer the research questions, and convenience sampling was used to recruit Women Knowledge Holders who were readily available and willing to contribute their insights. The study engaged 24 participants, representing three groups: five Grade 6 teachers, 10 Grade 6 learners and nine Women Knowledge Holders. Data analysis was done through thematic analysis. The findings revealed that the teachers interviewed lack knowledge of ethnomathematical approaches, Women Knowledge Holders can forster deeper connections between learners’ culture and mathematics. It was also found that Women Knowledge Holders did not recognise their cultural crafting practices as mathematical endeavors. The study recommended teacher trainings on ethnomathematical approaches, partnership and collaboration with Women Knowledge Holders, acknowledging, recording and preserving their mathematical contributions. Future research should focus on developing a culturally relevant mathematics framework with particular reference to Ndebele culture so that teachers can explore and understand the relationship between Ndebele culture, mathematics, teaching and learning, facilitating the implementation of ethnomathematical approaches.
Thesis (Ph.D. (Subject Education in Mathematics))--University of the Free State, 2024
Keywords: Ethnomathematics; Ethnomathematical approaches; Indigenous Knowledge Systems; Mathematical concepts and skills; Ndebele cultural artefacts; Ndebele mural art; Women knowledge holders